Kepraktisan Media Tutorial Pembelajaran Matematika Berbasis Komputer pada Materi Pokok Bangun Ruang - Baiq Dian Arianingsih; Arjudin Arjudin; Nourma Pramestie Wulandari; Nyoman Sridana (Griya Journal of Mathematics Education and Application, 2022)
Learning media have a contribution to the teaching and learning process, not only helping teachers deliver lessons but also providing added value in learning. One of the media that can be used as a solution as an interesting learning medium is a computer-based tutorial media of mathematics. This study aims at producing a practical computer-based tutorial media of mathematics. The subject of the study is the 30 students of IX-4 class of SMPN 1 Keruak, in which it is categorized as research and development by using the model ADDIE from Brunch. Furthermore, ADDIE is the acronym for analyze, design, development, implementation, and evaluation. The instrument used in collecting the data consists of a teacher-student practicality instrument. Based on the media, the assessment for the testing of practicality is in the category "very valid” for the teachers and students with 89% for teacher practitioners and 89 3% for student practitioners. Based on the result, it can be concluded that a computer-based tutorial media of mathematical learning that has been developed is feasible to use.